Measurement and simulation of temperature-dependent spontaneous Raman scattering of O2 including P and R branches. (March 2023) - Lill, Johannes; Dieter, Kevin; Koschnick, Konrad; Dreizler, Andreas; Magnotti, Gaetano; Geyer, Dirk
Highlights: O2 Raman spectra including P and R transitions are simulated and validated on new experimental data. The simulation includes spin-splitting of the rotational states, anharmonicities and scattering angle dependencies. Neglecting P and R transitions can lead to underestimation of O2 concentrations in high-temperature environments. Accurate modelling of O2 allows for precise temperature measurements in reactive flows by spectral fit. Abstract: Evaluation methods for species and temperature determination in gaseous mixtures using spontaneous Raman scattering require detailed information on the spectra of the involved species. For most diatomic and some triatomic molecules that are relevant in combustion processes (H2, N2, O2, CO, CO2, H2 O) these spectra can be simulated based on the underlying quantum mechanical processes. In contrast to the other diatomic molecules, the electronic ground state of oxygen has an electronic spin of S = 1 which leads to the tripling of transitions and the occurrence of P and R branches. Though being neglected so far due to their small effect size, these additional transitions change the spectral shape and the integrated signal intensity which can lead to inaccuracies in evaluation methods such as the hybrid matrix inversion or full spectral fit. In this paper, P and R branches were simulated and their effect on the ro-vibrational oxygen spectrum evaluated by comparison to high-resolution experimental spectra in temperatures up to over 2000 K. Spectral fitting of O2 using this simulation allows for temperature determination of gaseous mixtures with a uncertainty better than 10 K and no significant difference to temperatures determined with the more established fitting of N2 . Fitted temperatures deviate by 4 K or less when P and R transitions are considered but fitting quality improves significantly when including them in the simulation. More importantly, neglecting P and R transitions leads to an overestimation of the temperature-dependent Raman cross section of O2 which causes underestimations of O2 concentration measurements using the hybrid matrix inversion or full spectral fit method.